A Compact Wide-Band Hybrid Dielectric Resonator Antenna with Enhanced Gain and Low Cross-Polarization. (26th April 2017) - Dong, Feibiao; Xu, Limei; Lin, Wenbin; Zhang, Tianhong
Abstract : By loading two printed patches to the dielectric resonator antenna (DRA), a compact wide-band hybrid dielectric resonator antenna with enhanced gain and low cross-polarization is presented. The proposed antenna utilizes a combination of a rectangular dielectric resonator and two printed patches. Due to the hybrid design, multiple resonances were obtained. By adding two air layers between the dielectric resonator and the printed patches, the bandwidth has been significantly improved. Compared to the traditional hybrid dielectric resonator antenna, the proposed antenna can achieve wide bandwidth, high gain, low cross-polarization, and even small size simultaneously. The prototype of the proposed antenna has been fabricated and tested. The measured −10 dB return loss bandwidth is 25.6% (1.7–2.2 GHz). The measured antenna gains are about 6.3 and 8.2 dBi in the operating frequency band. Low cross-polarization levels of less than −28.5 dB and −43 dB in the E-plane and H-plane are achieved. Moreover, the overall dimensions of the antenna are only 67 × 67 × 34 (mm 3 ). The proposed antenna is especially attractive for small base antenna applications.